Selective production of furanic ethers from lignocellulosic biomass over mesoporous Zr-incorporated SBA-15 catalyst - Patil, Chetana R.; Rode, Chandrashekhar, V. (ChemistrySelect, 2018)
Etherification of furanic compounds such as furfuryl alcohol (FA) and 5-(Hydroxymethyl) furfural (5-HMF) to the corresponding ethers was successfully achieved over Zr-SBA-15 catalyst. For this purpose, various Zr-SBA-15 catalysts with different Zr/Si molar ratios in self-generated acidic environment were prepared by one-pot strategy in self-generated acidic environment. XRD analysis revealed the increase in the d-spacing from 9.021 nm for parent SBA-15 to 11.66 nm for Zr-SBA-15, confirming the incorporation of Zr into the framework without disturbing the mesoporous structure of SBA-15. For the lowest Zr concentration of 0.09 M, hexagonally ordered porous structure was found to be retained as confirmed by TEM while, increase in Zr/Si molar ratio to 0.14, resulted in loss of long range order mesoporosity. The presence of both Lewis and Bronsted acid sites in Zr-SBA-15 catalyst as evidenced by py-IR, were due to the introduction of Zr in the frame work of SBA-15. The co-existence of Lewis and Bronsted acid sites in Zr-SBA-15 was responsible to catalyze etherification of FA and esterification of levulinic acid producing 2-(Ethoxymethyl) furan and ethyl levulinate selectively, both of which are bio-derived fuel additives.

Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15

Single-pot alcoholysis of furfuryl alcohol to alkyl levulinates using heterogenized p-TSA catalyst** - Patil, Chetana R.; Kamble, Sanjay P.; Rode, Chandrashekhar V. (ChemistrySelect, 2021)
Synthesis of levulinate esters which are known to be excellent sustainable fuel additives, was achieved by alcoholysis of furfuryl alcohol over strong solid acid catalyst, prepared by copolymerization of p-toluenesulfonic acid with paraformaldehyde. Our catalyst possessed Bronsted acidity (3 mmol/g) with an excellent stability up to 220 degrees C. XPS, FT-IR and Pyridine-IR along with microanalysis studies confirmed the presence of terminal -SO3H functional groups responsible for Bronsted acidity in the catalyst. The catalyst was found to efficiently catalyze the alcoholysis of furfuryl alcohol to give alkyl levulinates under mild reaction conditions. The complete conversion of furfuryl alcohol with 96 % and 97 % selectivities to ethyl and butyl levulinates could be achieved using ethanol and butanol, respectively. Detailed study on effect of various reaction parameters like catalyst loading, reaction time and reaction temperature on conversion and product distribution was also carried out for the ethanolysis of furfuryl alcohol to ethyl levulinate. The catalyst could be easily recovered and recycled for five times successfully, with no loss in its original activity.
Keywords: Biomass; ethyl levulinate; Fuel additive; Furfuryl alcohol; heterogeneous catalysis